Renal expression of tissue factor pathway inhibitor and evidence for a role in crescentic glomerulonephritis in rabbits. - Erlich, J H (1996)
Tissue factor pathway inhibitor (TFPI) was demonstrated in the kidneys of normal rabbits and in a crescentic model of glomerulonephritis (GN), where fibrin is a key mediator of injury. In normal kidneys, TFPI was expressed in glomeruli, in intrarenal arteries and the interstitial capillary network. Evidence for TFPI synthesis in vivo was provided by in situ demonstration of TFPI mRNA in glomeruli and intrarenal vessels and by biosynthetic labeling of TFPI released from glomeruli in vitro. In fibrin-dependent crescentic GN, glomerular TFPI synthesis and expression was initially decreased (TFPI antigen at 24 h, 7.5 +/- 0.7 ng/10(3) glomeruli; normal, 11.1 +/- 0.9 ng/10(3) glomeruli, P < 0.02) and subsequently returned to normal values. Plasma TFPI levels increased progressively throughout the evolution of disease. In vivo inhibition of TFPI using an anti-TFPI antibody during the development of GN significantly increased glomerular fibrin deposition (GFD) and exacerbated renal impairment. Infusion of recombinant human TFPI significantly reduced development of GFD (fibrin scores, TFPI treated 0.82 +/- 0.11, control 1.49 +/- 0.14, P < 0.01), proteinuria and renal impairment. This data indicates that TFPI is synthesized and expressed in normal glomeruli and is down regulated in the early response to glomerular injury. Endogenous glomerular TFPI and treatment with recombinant TFPI reduces GFD and injury in fibrin dependent GN. TFPI has the potential to be of therapeutic benefit in the management of fibrin dependent human GN.